Randomised, double blind, placebo controlled comparison of ginkgo biloba and acetazolamide for prevention of acute mountain sickness among Himalayan trekkers: the prevention of high altitude illness trial (PHAIT) - Gertsch, Jeffrey H (BMJ Publishing Group Ltd., 2004)
Objective To evaluate the efficacy of ginkgo biloba, acetazolamide, and their combination as prophylaxis against acute mountain sickness. Design Prospective, double blind, randomised, placebo controlled trial. Setting Approach to Mount Everest base camp in the Nepal Himalayas at 4280 m or 4358 m and study end point at 4928 m during October and November 2002. Participants 614 healthy western trekkers (487 completed the trial) assigned to receive ginkgo, acetazolamide, combined acetazolamide and ginkgo, or placebo, initially taking at least three or four doses before continued ascent. Main outcome measures Incidence measured by Lake Louise acute mountain sickness score ≥ 3 with headache and one other symptom. Secondary outcome measures included blood oxygen content, severity of syndrome (Lake Louise scores ≥ 5), incidence of headache, and severity of headache. Results Ginkgo was not significantly different from placebo for any outcome; however participants in the acetazolamide group showed significant levels of protection. The incidence of acute mountain sickness was 34% for placebo, 12% for acetazolamide (odds ratio 3.76, 95% confidence interval 1.91 to 7.39, number needed to treat 4), 35% for ginkgo (0.95, 0.56 to 1.62), and 14% for combined ginkgo and acetazolamide (3.04, 1.62 to 5.69). The proportion of patients with increased severity of acute mountain sickness was 18% for placebo, 3% for acetazoalmide (6.46, 2.15 to 19.40, number needed to treat 7), 18% for ginkgo (1, 0.52 to 1.90), and 7% for combined ginkgo and acetazolamide (2.95, 1.30 to 6.70). Conclusions When compared with placebo, ginkgo is not effective at preventing acute mountain sickness. Acetazolamide 250 mg twice daily afforded robust protection against symptoms of acute mountain sickness.